Effects of intensified training and detraining on testicular function - Hall, H. L.; Flynn, M. G.; Carroll, K. K.; Brolinson, P. G.; Shapiro, S.; Bushman, B. A. (Clinical Journal of Sport Medicine, 1999)
OBJECTIVE: To examine the effects of an increased training load and period of detraining on testicular function in male distance runners. DESIGN: Multiple-group time-series design using a control group. SETTING: University of Toledo and Toledo Hospital. PARTICIPANTS: Eight male runners and eight age-matched sedentary control subjects. Subjects were considered fit for participation after a physical and genital examination conducted by a physician. INTERVENTION: Subjects provided blood and semen samples every 2 weeks for 8 weeks. The training regimen for the runners consisted of 2 weeks at normal training (NT), 2 weeks at 143% of NT (IT1), 2 weeks at 186% of NT (IT2), and 2 weeks at 50% of NT (RT). These percentages represent increases in training distance (volume). MAIN OUTCOME MEASURES: Within the context of this investigation, the following hypothesis was developed: increases or decreases in training would not significantly alter sperm count, density, motility, or morphology, or concentrations of reproductive hormones or cortisol in runners. RESULTS: There were no statistically significant differences observed between runners and control subjects for any of the reproductive hormones or cortisol. In addition, there was no significant treatment effect for sperm count, motility, or morphology. The sperm levels in two runners in this investigation dropped to oligospermatic levels after IT2; however, total sperm count increased in both runners after 2 weeks of RT. CONCLUSION: Four weeks of increased training and 2 weeks of reduced training did not significantly affect the subjects in this investigation. It is possible that a particular level or degree of training must be surpassed before any clinical alterations are evident. Future longitudinal studies are necessary to identify the extent to which endurance training may alter reproductive hormones and testicular function.